The Relationship Between Happiness at Work and Organizational Culture with Employee Performance at Fertilizer Distributors - Inats Tsuraiya Bintang Mahardika; Iranita Hervi Mahardayani (UIN Fatmawati Sukarno Bengkulu, 2026)
This study aims to determine whether happiness at work and organizational culture are related to employee performance in a fertilizer distributor company. Using a quantitative correlational design, the study involved 43 randomly selected employees. The instruments measured employees’ levels of workplace happiness, their perception of the organizational culture, and their daily performance achievements. The results reveal that neither happiness at work nor organizational culture is related to employee performance. Employees who reported higher levels of workplace happiness did not demonstrate better performance than their peers. Likewise, positive perceptions of organizational culture did not contribute to improvements in work quality, timeliness, or overall effectiveness. In general, employees were able to maintain stable performance levels even though their happiness and cultural perceptions were only in the moderate category. These findings indicate that employee performance in this company is likely influenced by other factors not examined in this study, such as workload, supervision systems, or work experience.